On the Relationship between Thinking and World Language Modeling: Based on Old Armenian Language Materials - Khachatryan, Lalik (Տիգրան Մեծ)
The analysis of the issues concerning the relationship between thinking and world language modelling showcases that linguistic modellings are at the forefront of the Old Armenian language and regulate the linguistic determinism and linguistic outlook of the society. Examinations of the Old Armenian sentence models and samples reveal that various qualitative manifestations of thinking existed in the 5th century, which are conditioned by the grammatical structure of Old Armenian, and the foreign-language influences. These were displayed both in translated literature and independent bibliographic works. Linguistic determinism as a synchronous maxim can also bear the stamp of foreign-language influences while genuinely preserving the peculiarities of national mentality.
Keywords: Epistemology; Old Armenian language (Grabar)